2016
DOI: 10.1049/iet-nbt.2016.0103
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using Mentha pulegium and investigation of their antibacterial, antifungal and anticancer activity

Abstract: A simple and eco-friendly method for efficient synthesis of stable colloidal silver nanoparticles (AgNPs) using extracts is described. A series of reactions was conducted using different types and concentrations of plant extract as well as metal ions to optimize the reaction conditions. AgNPs were characterized by using UV-vis spectroscopy, transmission electron microscopy, atomic force microscopy, dynamic light scattering, zetasizer, energy-dispersive X-ray spectroscopy (EDAX) and Fourier transform infrared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 23 publications
6
45
1
1
Order By: Relevance
“…AgNPs synthesized from the leaf extract of Mentha pulegium were found cytotoxic to Hela and MCF-7 cancer cells [10]. AgNPs were treated on MCF-7 cell line shows drastic changes in morphological characteristics.…”
Section: Anticancermentioning
confidence: 96%
See 2 more Smart Citations
“…AgNPs synthesized from the leaf extract of Mentha pulegium were found cytotoxic to Hela and MCF-7 cancer cells [10]. AgNPs were treated on MCF-7 cell line shows drastic changes in morphological characteristics.…”
Section: Anticancermentioning
confidence: 96%
“…Along with that cytoplasmic shrinkage and cell clustering was observed unlike the case in AgNPs treated normal cells. The cells were treated with 20 lg/mL concentration of AgNPs and kept for 48 h for further observation and found apoptosis of the cells [10]. AgNPs synthesized with Coriandrum sativum and Prosopis cineraria extract as a reducing agent showed anticancer activity against MCF-7 cancer cells [11,14].…”
Section: Anticancermentioning
confidence: 99%
See 1 more Smart Citation
“…46 With such a promise shown in previous studies, there has been an increased interest in the generation of green NPs that also have anticancer properties. For example, copper oxide NPs made by Rehana et al 47 and silver NPs produced by Kelkawi et al 48 that were both synthesized using different plant extracts showed attractive anticancer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Green synthesis methods are increasingly being investigated, using natural compounds such as mint fragrant [10], honey [11], white sugar [12], Arab rubber [13], corn dextrose [14], silkworm sericin [15] and glucose [16] as reducers. By synthesis using a spinning disk reactor with glucose as a reducing agent and starch, as a cheap and non-toxic stabilizer, nanoparticles up to 10 nm in diameter were obtained and remained stable over 40 days [17].…”
Section: Introductionmentioning
confidence: 99%